THE EFFECTIVENESS OF USING CROSSWORD PUZZLE GAME TO INCREASE STUDENTS’ VOCABULARY - Fajar Rizqi; Sriati Usman (e-Journal of ELTS (English Language Teaching Society), 2021)
The objective of this research is to find out whether Crossword Puzzle Game is effective to increase vocabulary of the eighth-grade students at SMPN 1 Ampibabo or not. This research applied a quasi-experimental research design, involves two groups, they were experimental and control groups. The sample was selected by cluster random sampling technique, and it was 20 students of class VIII A as the experimental class and 20 students of class VIII B as the control class. The instrument used for collecting data was a test. The test included pre-test and post-test, with the mean score 51.00 for experimental class, and 57.80 for control class on pre-test. While on post-test, 72.60 for experimental class, and 64.00 for control class. The data results from the test were analyzed statistically by applying the t-test formula. The results of the analysis showed that the value of t-counted (3.1) is higher than t-table (2.025). It means that the research hypothesis was accepted. In other words, applying Crossword Puzzle Game is effective to increase vocabulary of the eighth-grade students at SMPN 1 Ampibabo. The implication of this finding to the teaching of vocabulary is that the selection of the right learning method can affect the achievement of students and teachers are expected to foster learning motivation in students in various ways according to the ability of the teacher and attractive to students.